2022
DOI: 10.18502/ijdo.v14i1.8741
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Motivational Interviewing based on the Ability, Information and Motivation Model on Adherence to Treatment and Glycosylated Hemoglobin in Females with Type 2 Diabetes Mellitus

Abstract: Objective: The aim of this study was to determine the effectiveness of motivational interviewing based on the ability, information, and motivation (AIM) model on adherence to treatment and glycosylated hemoglobin (HbA1c) in female patients with type 2 diabetes. Materials and Methods: In this randomized controlled clinical trial 60 women with type 2 diabetes were randomly selected from the 73 patients who referred to the endocrinology department of Imam Hossein Hospital in Tehran province from December 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 0 publications
0
17
1
Order By: Relevance
“…In eight of 16 studies, self-compassion was shown to be related to an improvement in regimen adherence and HbA1C levels and an increase in various psychological well-being domains ( Ferrari et al, 2017 ; Jackson, 2018 ; Tanenbaum et al, 2018 ; Morrison et al, 2019 ; Ventura et al, 2019 ; Rahmani et al, 2020 ; Akbari et al, 2022 ; Loseby et al, 2022 ). One article ( Kılıç et al, 2022 ) did not support this and found that self-compassion did not uniquely predict variables such as depression, anxiety, and quality of life.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In eight of 16 studies, self-compassion was shown to be related to an improvement in regimen adherence and HbA1C levels and an increase in various psychological well-being domains ( Ferrari et al, 2017 ; Jackson, 2018 ; Tanenbaum et al, 2018 ; Morrison et al, 2019 ; Ventura et al, 2019 ; Rahmani et al, 2020 ; Akbari et al, 2022 ; Loseby et al, 2022 ). One article ( Kılıç et al, 2022 ) did not support this and found that self-compassion did not uniquely predict variables such as depression, anxiety, and quality of life.…”
Section: Resultsmentioning
confidence: 99%
“…Self-compassion was also found to be meaningfully associated with more optimal self-care behaviors ( Loseby et al, 2022 ). It is vital to understand this relationship, as improved self-care behaviors have been shown to improve regimen adherence and self-management behaviors which, in turn, reduce HbA1c levels ( Ferrari et al, 2017 ; Jackson, 2018 ; Rahmani et al, 2020 ; Loseby et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations